Antioxidant and the Dwarfing Candidate Gene of "Nantongxiaofangshi" (Diospyros kaki Thunb.). (25th November 2019) - Dong, Yuhan; Wang, Peihong; Jiang, Mengting; Qu, Shenchun
Abstract : The aims of this work were to identify genes related to dwarfing for subsequent dwarfing-related research in persimmon and evaluate the relationship between antioxidant activity, dwarf, and hormones of persimmon trees for analyzing the possible dwarf mechanism oxidation factors. In the present study, a transcriptome analysis of "Nantongxiaofangshi" was used to identify and clone 22 candidate genes related to gibberellin signal transduction pathways and synthetic pathway. The expression of these genes was assessed in two persimmon cultivars, "Dafangshi" and "Nantongxiaofangshi, " by RT-qPCR at different phenological stages and in response to the exogenous application of GA3 (GA treatment) and PAZ (paclobutrazol, a plant growth inhibitor, also called PP333 ). The results revealed differential expression of 14 of these 22 genes in the two varieties. Subsequently, endogenous hormone levels were assessed of the two varieties, along with the number of internodes and internode length. The results suggested that the persimmon could be used as a valuable and powerful natural candidate for providing information on the functional role of dwarfing.